Instrumental texture profile and microbiological evaluation of coalho cheese marketed in free fairs (Research, Society and Development, 2020)
The present work aims to evaluate the instrumental texture profile and the microbiological quality of rennet cheeses marketed in the open market in the city of Garanhuns-PE, thus verifying whether the products comply with the parameters required by current legislation. Six samples were collected as a consumer and analyzed for the instrumental texture profile, with the following attributes being studied: firmness, cohesiveness, adhesiveness and stickiness; and as for its microbiological quality in relation to the parameters of total coliforms, E. coli, Staphylococcus, Salmonella sp. Sample 5 showed the highest values of firmness, adhesiveness and guminess, in addition, it also showed the highest growth for total coliforms. However, with respect to the group of thermotolerant coliforms, all samples analyzed are in accordance with the limit established for this parameter. Sample (4) indicated the presence of  E.coli and samples 4 and 5 indicated the presence of Salmonella sp. In Staphylococus quantification it was observed that samples 2, 3 and 4 are not in accordance with the standard established by legislation. It can be concluded that, among the samples analyzed, only 1 and 6 are in accordance with the quality standards established by the legislation in relation to the microbiological analyzes performed